Assessing sarcopenic prevalence and risk factors in residential aged care: methodology and feasibility. Issue 3 (16th April 2014) - Henwood, Timothy R.; Keogh, Justin W.; Reid, Natasha; Jordan, Will; Senior, Hugh E.
Abstract : Background: Sarcopenia is a significant geriatric syndrome with both health care expenditure and personal burden. Most recently, the European Working Group in Sarcopenia in Older Adults has established a consensus definition and assessment criteria for sarcopenia that includes a below‐normal muscle mass and muscle function (either or both of below‐normal muscle strength and physical performance). Using these criteria, work is needed to identify the prevalence and risk factors among the old, and those most susceptible to sarcopenia, the very old. This manuscript describes the recruitment and data collection methodology, and direct burden to participants, among a very old cohort residing in a residential aged care (RAC) setting. Methods: Eleven RAC facilities participated in the study. Potential participants were identified by the facility service manager and then randomised into the study. All participants gave self or substitute decision maker consent. Participants undertook a single one on one assessment that included measures of sarcopenia, functional capacity, cognitive and nutritional health, falls, activity, facility and hospital history, physical activity and assessment burden. A sub‐study of physical activity and sedentary behaviours measured by activPAL3™ inclinometer was also conducted. Results: Of 709 residents, 328 were ineligible to participate. Two hundred and seventy‐three residents were randomised to the study and 102 gave informed or substitute decision maker consent. Participants were 84.5 ± 8.2 years of age and had been in care for 1, 204.2 ± 1, 220.1 days. The groups need for care was high (Aged Care Funding Instrument score of 2.6 ± 1.7) and they had a below‐normal functional (Short Physical Performance Battery summery score of 3.5 ± 2.4). The larger percentage of participants had no depression and normal cognitive capacity. A total of 33 residents participated in the activPAL study. Each assessment took an average of 27.0 ± 7.0 min, with a low assessment burden reported by participants. Conclusions: The successful assessment of sarcopenia and physical activity in a RAC setting is labour intensive to establish, but feasible to conduct. Low recruitment numbers and the restrictive exclusion criteria, may have limited the accuracy of this work. However, this work is a primary step in establishing the level of sarcopenia and its risk factors for those in end‐of‐life care.